2017
DOI: 10.26822/iejee.2017236121
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Teaching Informative Text through Processual Model on Reading Comprehsion Skills

Abstract: This study was carried out in order to search the effects of teaching informative text structures through processual model on the reading comprehension skills of 4 th grade students. The research was designed in accordance with experimental model with pre-test-post-test control groups. The study group of the study consisted of 62 fourth grade students who receive their education in 2012-2013 school year in a state school located in the province of Konya, Turkey. Teaching of the informative texts was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
(15 reference statements)
0
5
0
1
Order By: Relevance
“…Students in the treatment group, who were explicitly taught to synthesize details into main idea statements about the general topic, made significantly more improvement than students in the control group. Other researchers have found similar positive results for this type of main idea instruction, including with students who have diagnosed reading disabilities (Boudah, 2014; O'Connor et al, 2017; Sulak & Güneş, 2017; Van Den Broek et al, 2003).…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Students in the treatment group, who were explicitly taught to synthesize details into main idea statements about the general topic, made significantly more improvement than students in the control group. Other researchers have found similar positive results for this type of main idea instruction, including with students who have diagnosed reading disabilities (Boudah, 2014; O'Connor et al, 2017; Sulak & Güneş, 2017; Van Den Broek et al, 2003).…”
Section: Introductionmentioning
confidence: 53%
“…Consistent with the study's hypothesis, students who engaged in DC demonstrated statistically significant higher posttest scores on the main idea assessment than students in the control group. This finding was expected given that adaptive CAI programs has significantly improved a wide variety of literacy skills (Council III et al, 2016; Schechter et al, 2015; Shamir et al, 2017, 2018; Y. Wang, 2016) as well as that the DC program was grounded in a research‐based approach to main idea instruction (e.g., Boudah, 2014; Sulak & Güneş, 2017; Williams et al, 1983). This study's findings extends the success of adaptive CAI to main idea skills, which had not previously been tested.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We expanded previous studies in this field with some important aspects. First, there were only a few studies to explore the "pure" effects of the summarizing strategy, because it was usually developed in combination with other strategies (Sulak & Güneş, 2017). Second, the effects of summarizing training were most often studied in students with reading comprehension difficulties (Brown & Palincsar, 1984) or in students with learning disabilities (Solis et al, 2011), but not in a normative population -on all students of a classroom, which was the case in our study.…”
Section: The Problem Of Researchmentioning
confidence: 99%
“…Akan tetapi, seorang pembaca yang baik juga perlu paham bahwa setiap teks, baik teks fiksi maupun teks informasi, pasti memiliki struktur mikro dan makro. Pada level mikro, struktur teks dikenal sebagai pembentukan arti kata, klausa dan kalimat, sedangkan pada level makro, struktur ini mencakup arti paragraf, bagian terpenting dari paragraf ataupun keseluruhan isi wacana, dan termasuk juga struktur organisasi paragraf (Sulak & Güneş, 2017). Ketika proses memahami bacaan dilakukan, seorang individu akan mendalami kedua struktur tersebut sambil menerapkan background knowledge ini.…”
Section: Pembahasanunclassified